Aktivitas Mengamalkan Ayat-Ayat Syifa’ (Obat) dan Pengaruhnya terhadap Kesembuhan Jasmani pada Wanita Pra Lansia di Desa Ulak Teberau - Assenang, Siti; Noupal, Muhammad; Ilyas, Deddy (Jurnal Riset Agama, 2024)
The purpose of this research is to find out the activities of reading the verses of shifa' on physical healing and to find out what are the factors that influence the activities of reading the verses of shifa' which affect physical health in pre-elderly women in Ulak Teberau Village. The type of research used in this research is qualitative research. The form of this research is afield study (field research) and the research model uses a case study with data collection techniques using observation, interviews and documentation. From the results of the study, seen from the physical condition of 3 subjects of pre-elderly mothers in Ulak Teberau Village, before reading and practicing the verses of shifa' and after reading and practicing the verses of shifa' for 3 weeks experienced significant changes and reduced pain in the limbs. As for the factors that influence the activities of reading and practicing verses of shifa’ on pre-elderly women in Ulak Teberau Village, namely there are factors: Having faith and faith, having consistency in practicing the verses of shifa ', understanding the content of the verses of shifa', having a specific disease.